Efficacy and safety of antibody-drug conjugates in the treatment of advanced urological cancers: a systematic review and a meta-analysis - Liu, Tian; Xie, Xiao; Ren, Yangz-Zi; Li, Zongyu; Cai, Maoping; Yu, Yuzhong; Zhuo, Lin (Frontiers in Pharmacology, 2025)
BackgroundAntibody-drug conjugates (ADCs) offer novel therapeutic options for advanced urological cancers, but their efficacy and safety vary across cancer types. Many non-urothelial cancer ADC trials are small, nonrandomized studies with limited validated evaluation indicators. The purpose of this study is to evaluate the efficacy and safety of ADCs across various urological cancers.MethodsRelevant studies were identified through searches in Embase, PubMed, Web of Science, Cochrane Library, CNKI, VIP database and WanFang dataset, including randomized controlled trials, single-arm studies, and retrospective analyses on ADCs for advanced urological cancers. RoB 2.0, MINORS, and NOS were used for quality assessment, with R 4.4.0 for data analysis.ResultsThis meta-analysis included 46 studies with 3,250 patients, covering urothelial cancer (29 studies), renal cell carcinoma (5 studies), testicular cancer (2 studies), and metastatic castration-resistant prostate cancer (10 studies). Three ADCs for urothelial cancer have received approval, including enfortumab vedotin (EV), sacituzumab govitecan (SG), and the HER2-ADC vedicilizumab (RC-48)/disitamab vedotin (DV). For urothelial cancer, the pooled overall response rate (ORR) was 43% (95% CI: 39%–47%) and disease control rate (DCR) was 76% (95% CI: 71%–80%). Median overall survival (OS) and progression-free survival (PFS) were 11.55 months (95% CI: 10.63–12.47) and 5.52 months (95% CI: 5.32–5.72) for enfortumab vedotin (EV), and 15.30 months (95% CI: 11.21–19.40) and 5.80 months (95% CI: 4.88–6.72) for DV. DV combined with immunotherapy achieved a pooled median PFS of 9.78 months (95% CI: 7.73–11.83). For renal cell carcinoma, the ORR was 6% (95% CI: 2%–10%) with median OS of 12.71 months (95% CI: 9.67–15.75). For metastatic castration-resistant prostate cancer, ADC efficacy was higher in chemotherapy-experienced patients (ORR: 17% vs. 5%).ConclusionADCs demonstrate efficacy and safety in treating urological cancers, but further clinical trials are needed, particularly for renal, testicular, and prostate cancers, to support personalized treatment strategies.